Removal of arsenic from liquid blister copper during remelting in an induction vacuum furnace - Łabaj J.; Blacha L.; Smalcerz A.; Chmiela B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Using a reduced pressure during the smelting and refining of alloys removes dissolved gasses, as well as impurities with a high vapor pressure. When smelting is carried out in vacuum induction furnaces, the intensification of the discussed processes is achieved by intensive mixing of the bath, as well as an enhanced mass exchange surface (liquid metal surface) due to the formation of a meniscus. This is due to the electromagnetic field applied to the liquid metal. This study reports the removal of arsenic from blister copper via refining in an induction vacuum furnace in the temperature range of 1423– 1523 K, at operating pressures from 8 to 1333 Pa. The overall mass transfer coefficient kAs determined from the experimental data ranged from 9.99·10-7 to 1.65·10-5 ms-1. Arsenic elimination was largely controlled by mass transfer in the gas phase. The kinetic analysis indicated that the arsenic evaporation rate was controlled by the combination of both liquid and gas-phase mass transfer only at a pressure of 8 Pa.